Contemporary tectonic stress field in the Himalaya-Tibet orogen: a view from 2D finite element modeling - Chamlagain, D; Hayashi, D (Journal of Nepal Geological Society, 2008)
The Himalaya-Tibet orogen and surrounding regions demonstrate complex contemporary tectonic stress field that reflects present-day geodynamics of the region. Because of underthrusting of the Indian plate below the Eurasian plate thrust faults are propagating to the foreland side of the Himalaya indicating southernmost front as a most active zone. This is also shown by focal mechanism solution of a moderate to large earthquakes that are mainly thrust type events. However, there are some events along the transverse fault indicating strike-slip motion. On the other hand, the entire Tibetan Plateau is characterized by extensional tectonics evidenced by normal and strike-slip events. Using different types of tectonic stress indicator (earthquake focal mechanisms, well bore breakouts and drilling-induced fractures, in-situ stress measurements; e.g., overcoring, hydraulic fracturing, borehole slotter; young geologic data e.g., fault-slip analysis and volcanic vent alignments), World Stress Map (WSM) project has presented an extensive data set on stress field in the Himalayan-Tibet region. These data suggest that the direction of maximum horizontal compressive stress (SHmax) is almost parallel to the direction of plate motion. SHmax trajectories radiate laterally from the Tibetan Plateau to the northern, eastern, and southeastern part of the Chinese mainland. However, the minimum horizontal compressive stress (SHmin) direction is arc convex outward from the Tibetan Plateau. For the Himalaya, SHmax are oriented in the NE direction in NW Himalaya, NS in central Himalaya and NW direction in eastern Himalaya. However, eastern syntaxis shows sharp bending of stress trajectories towards southeast direction. In general, SHmax shows fan shaped stress field. In this study, taking observed SHmax as a proxy, it is aimed to study stress sources, neotectonics and plate kinematics in the Himalayan-Tibet orogen using two-dimensional elastic finite element method under plane stress condition. Furthermore, comparison of recent stress observations with results of stress modeling is made to refine our understanding of geodynamics acting in this region. This study mainly concludes that the convergence normal to the orogen is essential to reproduce observed SHmax, which in turn controls the magnitude and orientation of SHmax. The kinematics equivalent to east-west tectonic escape did not simulate the observed stress field. Therefore, it is understood that the present day stress field is mainly governed by the southeastward tectonic escape of the Tibetan crust rather than eastward extrusion, and is also supported by GPS data. There is, however, significant increase in SHmax magnitude with higher crustal depth because of stress amplification. Incorporation of suture zones in the models did not change the orientation of SHmax significantly. Considering these facts, ‘continuum tectonic model’ is more preferable than the ‘block tectonic model’ for the active deformation of the Tibetan Plateau. While the models from this study provide a reasonable interpretation of the stress orientation and seismicity observed in the India-Eurasia collision zone, some part of the model lacks good fit with the observed data. This could be due to perturbation in the stress field associated with either local or regional structures and their present movement or far field plate kinematics of the Southeast Asia. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.5